First successful domestication of a white strain of Auricularia cornea from Thailand - Bandara, A.R.; Mortimer, P.E.; Vadthanarat, S.; Xingrong, P.; Karunarathna, Samantha C; Hyde, Kevin D.; Kakumyan, P.; Xu, J.C. (Mushroom Research Foundation, 2020)
Intraspecies colour variations in cultivated edible mushrooms present novel and potentially valuable alternatives to the research and cultivation industries. In this study, we collected, identified, and domesticated a white strain of Auricularia cornea from Thailand. The brown strain of A. cornea is one of the top two species of Auricularia cultivated and traded in Asia. Since both white and brown phenotypes of A. cornea belong to a single species, we established their similarities or differences. Both morphological characteristics and phylogenetic analysis of ITS rDNA sequence data were used to confirm the taxonomic placement of the white A. cornea strain in the same clade with the brown A. cornea. Nutritional analysis showed that fat, fiber, protein, and total soluble sugar contents of the white A. cornea were significantly higher than the commercially used brown strain. The melanin content of the white strain of A. cornea (less than 1.5 mg/100g) was not significantly different from that of the brown strain. This discovery may create new opportunities for the mushroom growing industry and for smallholder farmers in Asia.